Effects of Transient and Persistent Anti-drug Antibodies to Certolizumab Pegol: Longitudinal Data from a 7-Year Study in Crohn's Disease. Issue 7 (July 2017) - Sandborn, William J.; Wolf, Douglas C.; Kosutic, Gordana; Parker, Gerry; Schreiber, Stefan; Lee, Scott D.; Abraham, Bincy; Afzali, Anita; Arsenescu, Razvan I.; Gutierrez, Alexandra; Spearman, Marshall; Coarse, Jason; et al.
Abstract : Background: Anti-drug antibodies (ADAbs) may decrease the efficacy of biologics and increase the risk of adverse events. A single positive test may not preclude further treatment because of variations in assays used, test timing, and patient variables. We evaluated the longitudinal patterns of immunogenicity during 7 years of antitumor necrosis factor-alpha drug certolizumab pegol (CZP) treatment for moderate-to-severe Crohn's disease. Methods: PRECiSE 3 patients (n = 595) received open-label CZP 400 mg every 4 weeks up to 7 years. CZP–ADAb expression, plasma CZP concentration, Harvey-Bradshaw Index, C-reactive protein, and fecal calprotectin concentrations were measured multiple times. Longitudinal data, examined for CZP–ADAb positivity and categorized as transient (with temporary/no effect on CZP concentration), persistent, or negative, were correlated with clinical and biological variables. Results: Of the CZP–ADAb–positive patients, 40 (22.6%) had transient CZP–ADAbs and 94 (77.4%) had persistent CZP–ADAbs. Demographic characteristics were similar between groups. Median C-reactive protein and fecal calprotectin were higher ( P < 0.05 at some visits) and plasma CZP concentrations were significantly lower ( P < 0.0001 at all visits) in the persistent CZP–ADAb–positive group relative to the CZP–ADAb–negative group. Transient CZP–ADAb–positive and CZP–ADAb–negative patients had similar plasma CZP, C-reactive protein, and fecal calprotectin concentrations. Median Harvey-Bradshaw Index scores and rates of adverse events were similar among groups. Conclusions: This analysis demonstrates that persistent CZP–ADAb has negative effects on drug levels and efficacy, whereas transient expression may not. Serial measurements may be needed to characterize ADAb positivity.www.clinicaltrials.gov, Number NCT00160524. Abstract : Article first published online 13 April 2017.Supplemental Digital Content is Available in the Text.